A core-shell structured SiC@C nanowire quasi-array and its preparation method and application

By covering the surface of SiC nanowires with sulfur-doped PEDOT layer to form a SiC@C nanowire quasi-array with core-shell structure, the problem of mismatch in the positive and negative electrode capacity in the Zn ion hybrid supercapacitor is solved, and high energy density and cycling stability are achieved. Improves charge storage efficiency and electrode dynamics characteristics.

CN115020114BActive Publication Date: 2025-01-14NINGBO UNIVERSITY OF TECHNOLOGY +1

Patent Information

Application Number
CN202210605950.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-05-31
Publication Date
2025-01-14
Estimated Expiration
2042-05-31

AI Technical Summary

Technical Problem

The existing Zn ion hybrid supercapacitors have poor overall performance due to mismatch in positive and negative electrode capacity, and the micropores generated during polymer carbonization lead to low charge storage efficiency and capacity loss.

Method used

SiC@C nanowire quasi-array with core-shell structure is used as the positive electrode material. By covering the PEDOT layer on the surface of the SiC nanowire and doping it with sulfur, a hierarchical structure is formed to improve conductivity and energy storage surface area, and the negative electrode with zinc sheet and The electrolyte with a concentration of 5-8M ZnCl2 is assembled to achieve the matching of positive and negative electrode capacity.

Benefits of technology

The high energy density and good cycle stability of zinc ion hybrid supercapacitors are achieved, and the charge storage efficiency and electrode dynamics characteristics are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115020114B_ABST
    Figure CN115020114B_ABST
Patent Text Reader

Abstract

The present invention relates to a SiC@C nanowire quasi-array with a core-shell structure and a preparation method and application thereof, and belongs to the technical field of nanomaterials. The present invention discloses a SiC@C nanowire quasi-array with a core-shell structure, wherein the phase composition of SiC in the SiC@C nanowire quasi-array is 3C-SiC, and the C of the shell layer is a carbon material doped with sulfur after freeze-drying and carbonization of a PEDOT layer. The present invention also discloses a preparation method of a SiC@C nanowire quasi-array with a core-shell structure, wherein the preparation method comprises: covering the pretreated carbon cloth on the crucible mouth containing polysilazane and melamine powder, heating in a high-temperature atmosphere furnace, and cooling to obtain a carbon cloth depositing a SiC quasi-array; arranging the carbon depositing SiC nanowires in a reaction vacuum chamber, inducing gaseous EDOT into the reaction vacuum chamber, and introducing gaseous FeCl3 into the reaction vacuum chamber to deposit a SiC@PEDOT nanowire quasi-array, and washing, freeze-drying, and carbonizing to obtain a sulfur-doped SiC@C nanowire composite material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of nanomaterials and relates to a SiC@C nanowire quasi-array with a core-shell structure and a preparation method and application thereof. Background Art

[0002] With the rapid development of new energy vehicles and portable electronic products, the requirements for energy supply devices are getting higher and higher, and the development of new and efficient energy storage devices is urgent. At present, researchers have developed various electrochemical energy storage devices, such as metal ion batteries, metal air batteries, flow batteries and supercapacitors. However, few devices meet the requirements of high energy / power density and long cycle stability at the same time. Zn ion hybrid supercapacitors (Zn-HSCs), as a new energy storage device, have attracted much attention due to the advantages of Zn element being non-toxic, abundant in source, and low redox potential (-0.76V vs SHE). In addition, the rapid plating / stripping process of Zn ions on the Zn anode can obtain the required high energy density, and the highly reversible adsorption / desorption of Zn ions on the carbon cathode gives extremely excellent power density.

[0003] At present, the biggest problem facing Zn-ion hybrid supercapacitors is still the problem of positive and negative electrode capacity matching, that is, the capacity of the carbon positive electrode does not match the high capacity of the Zn negative electrode, which makes the overall performance of Zn-HSCs devices often far below the expected value. Recently, the addition of impurity atoms (such as N, B, P, S and O) to porous carbon is considered to be an effective strategy to significantly improve the cathode capacitance. Accordingly, direct carbonization of polymers rich in impurity atoms (such as polyaniline (PANI), naphthol (PPy) and polythiophene (PTh)) can simultaneously introduce impurity atoms with a specific concentration. For example, Lu et al. reported a series of impurity-atom-doped porous carbons with a high specific capacitance of 464F / g (0.2A / g) and an energy density of up to 16.2Wh / kg at a power density of 50W / kg; Deka et al. reported N-doped porous carbon for high-efficiency supercapacitors with a high specific capacitance of 445F / g (1A / g). It is confirmed that the chemical bonds generated between C atoms and impurity atoms can serve as important active sites. However, most of the pore structures produced during the carbonization of polymers are micropores, which leads to low charge storage efficiency. In addition, micropores are not conducive to the solvent Zn 2+ The ion screening effect will directly cause serious capacity loss. Therefore, the energy density of Zn-HSCs devices reported so far is significantly lower than the theoretical value. Summary of the invention

[0004] The purpose of the present invention is to address the above-mentioned problems existing in the prior art, and propose a positive electrode material with a SiC@C nanowire quasi-array of a core-shell structure, and assemble it into a zinc ion hybrid supercapacitor with matched positive and negative electrode capacities.

[0005] The purpose of the present invention can be achieved by the following technical solutions:

[0006] A SiC@C nanowire quasi-array with a core-shell structure, wherein the phase composition of SiC in the SiC@C nanowire quasi-array is 3C-SiC, and C in the shell layer is a carbon material doped with sulfur after a PEDOT layer is freeze-dried and carbonized.

[0007] Preferably, the SiC@C nanowire quasi-array has an aspect ratio of ≥30, a wire diameter of 500-800 nm, and a pore length of 13-18 μm.

[0008] Preferably, the PEDOT layer is covered on the surface of the SiC nanowires by performing oxidative chemical vapor deposition (oCVD) in a reaction vacuum chamber.

[0009] More preferably, the thickness of the PEDOT layer is 40 to 60 nm.

[0010] The present invention also discloses a method for preparing a SiC@C nanowire quasi-array with a core-shell structure, the preparation method comprising: covering the pretreated carbon cloth on the crucible mouth containing polysilazane and melamine powder, heating in a high-temperature atmosphere furnace, and cooling to obtain the carbon cloth deposited with SiC quasi-array; arranging the carbon deposited with SiC nanowires in a reaction vacuum chamber, inducing gaseous EDOT into the reaction vacuum chamber, introducing gaseous FeCl3 into the reaction vacuum chamber and then depositing the SiC@PEDOT nanowire quasi-array, and washing, freeze-drying, and carbonizing to obtain the sulfur-doped SiC@C nanowire composite material.

[0011] Preferably, the pretreatment of the carbon cloth comprises washing the carbon cloth in dilute hydrochloric acid and deionized water in sequence and then drying it.

[0012] Preferably, the mass ratio of polysilazane to melamine is (1-5):1.

[0013] Preferably, the heating temperature in the high temperature atmosphere furnace is 1400-1700°C, the time is 1-3h, and the heating rate is 30-40°C / min.

[0014] More preferably, the heating temperature is 1530-1760°C.

[0015] Preferably, the vacuum degree in the oCVD chamber is 10 -4 MPa, the deposition temperature is 90-110℃, and the deposition time is 0.5-5h.

[0016] Preferably, the vaporous EDOT is obtained by evaporating at 90-95°C.

[0017] Preferably, the gaseous FeCl3 is obtained after evaporation at 220-230°C.

[0018] Preferably, the freeze-drying temperature is -70 to -90°C and the time is 40 to 60 hours.

[0019] Preferably, the carbonization temperature is 700-900°C and the time is 0.5-3h.

[0020] During the carbonization process, PEDOT is transformed into a sulfur-doped shell C. The sulfur source is the sulfur element contained in PEDOT itself, so it has great advantages in terms of doping depth and uniformity. In addition, sulfur doping improves the electrical conductivity of the carbon material.

[0021] The present invention also discloses a zinc ion hybrid supercapacitor, in which the positive electrode material is a SiC@C nanowire quasi-array with a core-shell structure, the negative electrode is a zinc sheet, and the electrolyte is ZnCl2 with a concentration of 5-8M.

[0022] Preferably, the electrolyte of the zinc ion hybrid supercapacitor has a concentration of 5-6M ZnCl2.

[0023] The zinc ion hybrid supercapacitor of the present invention has a wide potential window and high energy density, and maintains good cycle stability.

[0024] Compared with the prior art, the present invention has the following beneficial effects:

[0025] 1. The core-shell structured SiC@C nanowire quasi-array of the present invention has a hierarchical structure, a large specific surface area, excellent conductivity, and interface functionalization, which is beneficial to promoting the rapid transport of ions / electrons.

[0026] 2. The core-shell structured SiC@C nanowire quasi-array of the present invention has a sulfur-doped shell layer C on the SiC surface. The porous carbon layer is beneficial to increasing the surface area for energy storage. Sulfur doping can modify the carbon structure to increase conductivity and improve the power characteristics of the supercapacitor.

[0027] 3. The zinc ion hybrid supercapacitor of the present invention, which is assembled from a positive electrode material of a core-shell structured SiC@C nanowire quasi-array, a zinc sheet negative electrode, and an electrolyte with a concentration of 5-8MZnCl2, has matching positive and negative electrode capacities and has high energy density and good cycle stability. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] Figure 1 This is a transmission electron microscope image of the SiC@C nanowire quasi-array with a core-shell structure in Example 1 of the present invention.

[0029] Figure 21 is the cyclic voltammetry curve of the SiC@C nanowire quasi-array with a core-shell structure in Example 1 of the present invention from 10 mV / s to 200 mV / s.

[0030] Figure 3 1 is a curve showing the relationship between the scan rate and the discharge current of the SiC@C nanowire quasi-array with a core-shell structure in Example 1 of the present invention.

[0031] Figure 4 This is the Nyquist diagram of the SiC@C nanowire quasi-array with core-shell structure in detections 1, 2 and 3 of Example 1 of the present invention tested under a three-electrode system.

[0032] Figure 5 The points of the hybrid supercapacitor assembled with the SiC@C nanowire quasi-array of the core-shell structure in Application Example 1 of the present invention under different potential ranges are windows.

[0033] Figure 6 This is the specific capacitance curve of the hybrid supercapacitor assembled with the SiC@C nanowire quasi-array of the core-shell structure in Application Example 1 of the present invention.

[0034] Figure 7 The hybrid supercapacitor assembled with SiC@C nanowire quasi-array of core-shell structure in Application Example 1 of the present invention is 2 mA / cm 2 Device cycling stability curve measured at a current density of .

[0035] Figure 8 This is a curve showing the corresponding relationship between energy density and power density of the hybrid supercapacitor assembled with SiC@C nanowire quasi-array of core-shell structure in Application Example 1 of the present invention. DETAILED DESCRIPTION

[0036] The following are specific embodiments of the present invention, which further describe the technical solutions of the present invention, but the present invention is not limited to these embodiments.

[0037] Example 1

[0038] The 4×4 cm carbon cloth was ultrasonically cleaned in dilute hydrochloric acid and deionized water in turn and then dried. Then the carbon cloth was covered with polysilazane and melamine powder with a mass ratio of 3:1, placed in a high-temperature atmosphere furnace and heated at 1550°C for 120 minutes, with a heating rate of 38°C / min, and cooled to obtain the carbon cloth deposited with SiC nanowires. The carbon deposited with SiC nanowires was arranged in a reaction vacuum chamber, and the vapor EDOT obtained by evaporation at 90°C was induced into the reaction vacuum chamber. After the vapor FeCl3 obtained by evaporation at 230°C was introduced into the oCVD chamber, the vacuum was 10 -4MPa, deposited at 100℃ for 1h to obtain SiC / PEDOT nanowire quasi-array, washed with water and freeze-dried at -80℃ for 48h, then carbonized in a tube furnace at 750℃ for 50min to obtain sulfur-doped SiC&C nanowire quasi-array, as shown in the TEM image Figure 1 As shown, it can be found that the SiC&C nanowire quasi-array is a core-shell structure.

[0039] The performance of the prepared SiC&C nanowire quasi-array with core-shell structure was tested.

[0040] Test 1:

[0041] The supercapacitor composed of the SiC@C nanowire quasi-array obtained in Example 1, a platinum counter electrode, and an Ag / AgCl reference electrode was placed in 1M ZnCl2 and tested in a three-electrode system. The cyclic voltammetry curve and discharge current curve of the three-electrode performance test are shown in Figure 2. Figure 2-3 As shown, Figure 2 This is the cyclic voltammetry curve of the SiC@C electrode (scan rate is 10-200 mV / s). The specific capacitance of the SiC@C electrode can be calculated to be 38.2 mF / cm under the condition of 10 mV / s by using the CV curve area. 2 When the scan rate is increased from 10mV / s to 100mV / s, the specific capacitance of SiC@C is still 29.8mF / cm 2 , showing the good rate performance of the electrode. It shows that the electrode has a high energy storage capacity. Figure 3 This is the relationship curve between discharge current and scan rate. In the scan rate range from 10 to 1000 mV / s, the discharge current can maintain a good linear relationship, indicating that the SiC@C electrode has good electrode kinetic characteristics.

[0042] Test 2:

[0043] The SiC@C nanowire quasi-array obtained in Example 1 was tested according to the method of test 1, except that the electrolyte was replaced with 1M ZnSO4. The performance test was carried out under the three-electrode system, and the specific capacitance at 100mV / s was 20.5mF / cm 2 .

[0044] Test three:

[0045] The SiC@C nanowire quasi-array obtained in Example 1 was tested according to the method of test 1, except that the electrolyte was replaced with 1M H2SO4. The performance test was carried out under the three-electrode system, and the specific capacitance at 100mV / s was 13.1mF / cm 2 .

[0046] Figure 4It is the Nyquist diagram of the tests in the above detections 1, 2 and 3. The intersection values ​​of the electrode with the horizontal axis are all less than 3Ω, and the electrode has a very small ohmic resistance.

[0047] Example 2

[0048] Compared with Example 1, the difference is that the carbonization temperature is 900°C. The specific capacitance at 100 mV / s in the three-electrode system is 22.7 mF / cm 2 .

[0049] Example 3

[0050] Compared with Example 1, the difference is that the carbonization temperature is 700°C. The specific capacitance at 100 mV / s in the three-electrode system is 24.6 mF / cm 2 .

[0051] Example 4

[0052] Compared with Example 1, the difference is that the carbonization temperature is 600°C. The specific capacitance at 100 mV / s in the three-electrode system is 18.4 mF / cm 2 .

[0053] Example 5

[0054] Compared with Example 1, the difference is that the carbonization temperature is 950°C. The specific capacitance at 100 mV / s in the three-electrode system is 20.1 mF / cm 2 .

[0055] Application Example 1

[0056] The SiC&C nanowire quasi-array obtained in Example 1 was used as the positive electrode, the zinc sheet was used as the negative electrode, and the electrolyte was 6MZnCl2 to assemble a SiC@C / / Zn hybrid supercapacitor.

[0057] Figure 5 The potential window widening test of the hybrid supercapacitor of this embodiment shows that the potential window of the assembled supercapacitor is widened from 1V to 1.8V, which is beneficial to improving the energy density of the assembled device. Figure 6 The specific capacitance at different current densities is shown in Figure 2. 2 The specific capacitance is 22.8mF / cm 2 When the current density is increased to 8 mA / cm 2 , the specific capacitance still retains 56%, indicating that the electrode has excellent rate performance. Figure 7 2mA / cm 2The cycling stability diagram of the GCD test in the potential window of 0-1.8 V at a current density of 2.5 V was shown. The results show that the capacitance retention rate of Zn-HSCs is about 97.18% after 5000 cycles. Figure 8 The relationship between the energy density and power density of the assembled hybrid supercapacitor is shown in Figure 2. 2 The energy density is 10.6 μWh / cm at power density 2 .

[0058] Application Example 2

[0059] Compared with Application Example 1, the difference is that the electrolyte is 4M ZnCl2. 2 The specific capacitance at current density is 20.5mF / cm 2 .

[0060] Application Example 3

[0061] Compared with Application Example 1, the difference is that the SiC&C nanowire quasi-array obtained in Example 2 is used as the positive electrode. 2 The specific capacitance at current density is 20.7mF / cm 2 .

[0062] Application Example 4

[0063] Compared with Application Example 1, the difference is that the SiC&C nanowire quasi-array obtained in Example 3 is used as the positive electrode. 2 The specific capacitance at current density is 21.0mF / cm 2 .

[0064] Application Example 5

[0065] Compared with Example 8, the difference is that the SiC&C nanowire quasi-array obtained in Example 4 is used as the positive electrode. 2 The specific capacitance at current density is 18.1mF / cm 2 .

[0066] Application Example 6

[0067] Compared with Application Example 1, the difference is that the SiC&C nanowire quasi-array obtained in Example 5 is used as the positive electrode. 2 The specific capacitance at current density is 19.4mF / cm 2 .

[0068] Comparative Example 1

[0069] Compared with Example 1, the difference is that SiC nanowires are directly used as electrode materials, and the performance test is carried out under the three-electrode system. 0.2mA / cm 2 The specific capacitance of the lower SiC@C electrode is 9.7mF / cm 2 .

[0070] Application Comparative Example 1

[0071] Compared with Application Example 1, the difference is that the material prepared in Comparative Example 1 is used as the positive electrode. 2 The specific capacitance at current density is 4.8mF / cm 2 .

[0072] The specific embodiments described herein are merely examples of the spirit of the present invention. Those skilled in the art may make various modifications or additions to the specific embodiments described or replace them in similar ways, but they will not deviate from the spirit of the present invention or exceed the scope defined by the appended claims.

Claims

1. A method for preparing a core-shell structured SiC@C nanowire quasi-array, characterized in that: The preparation method comprises: covering the pretreated carbon cloth on the crucible mouth containing polysilazane and melamine powder, heating in a high-temperature atmosphere furnace, and cooling to obtain the carbon cloth deposited with SiC quasi-array; arranging the carbon deposited with SiC nanowires in a reaction vacuum chamber, inducing gaseous EDOT into the reaction vacuum chamber, introducing gaseous FeCl3 into an oCVD cavity and then depositing the SiC@PEDOT nanowire quasi-array, and then washing, freeze-drying, and carbonizing to obtain the sulfur-doped SiC@C nanowire quasi-array; The phase composition of SiC in the SiC@C nanowire quasi-array is 3C-SiC, and C in the shell layer is a carbon material doped with sulfur after the PEDOT layer is freeze-dried and carbonized.

2. The method for preparing a core-shell structured SiC@C nanowire quasi-array according to claim 1, characterized in that: The aspect ratio of the SiC@C nanowire quasi-array is ≥30, the wire diameter is 500-800nm, and the hole length is 13-18μm.

3. The method for preparing the core-shell structured SiC@C nanowire quasi-array according to claim 1, characterized in that: The PEDOT layer is covered on the surface of the SiC nanowire after being deposited by oxidation chemical vapor in a reaction vacuum chamber.

4. The method for preparing a core-shell structured SiC@C nanowire quasi-array according to claim 1, characterized in that: The mass ratio of the polysilazane to melamine is (1-5):

1.

5. The method for preparing the core-shell structured SiC@C nanowire quasi-array according to claim 1, characterized in that: The heating temperature is 1400-1700° C., the time is 1-3 hours, and the heating speed is 30-40° C. / min.

6. The method for preparing a core-shell structured SiC@C nanowire quasi-array according to claim 1, characterized in that: The vacuum degree in the oCVD chamber is 10 -4 MPa, the deposition temperature is 90~110℃, and the deposition time is 0.5~5h.

7. The method for preparing a core-shell structured SiC@C nanowire quasi-array according to claim 1, characterized in that: The freeze-drying temperature is -70 to -90°C and the time is 40 to 60 hours.

8. The method for preparing a core-shell structured SiC@C nanowire quasi-array according to claim 1, characterized in that: The carbonization temperature is 700-900° C., and the time is 0.5-3 h.

9. A core-shell structured SiC@C nanowire quasi-array, characterized in that: The nanowire is prepared by the method for preparing a SiC@C nanowire quasi-array with a core-shell structure as claimed in any one of claims 1 to 8.

10. A zinc ion hybrid supercapacitor, characterized in that: The positive electrode material in the zinc ion hybrid supercapacitor is the SiC@C nanowire quasi-array with a core-shell structure as described in claim 9, the negative electrode is a zinc sheet, and the electrolyte has a concentration of 5-8M ZnCl2.

Citation Information

Patent Citations

  • Preparation method for conductive polymer nanotubes with high length-diameter ratio

    CN108929429A

  • Conductive ternary composite material as well as preparation method and application thereof

    CN111540899A

Cited By

  • Wave-absorbing core-shell structure super-surface composite material for unmanned aerial vehicle and preparation method thereof

    CN120757395A